Compost derived from local organic materials as source of plant nutrients. (December 2018) - Riwandi,; Handajaningsih, M; Prasetyo,; Hasanudin,
Abstract: The aim of this study was to produce high quality compost and to interpret data during the composting process. Compost materials used in the composting were carbon-rich materials, nitrogen, and goat dung, added with topsoil from garden, rice husk, cow urine, and EM4 (microorganism effective 4). The method used was Indore method. The principle of this method is by placing every material in layers in a certain width, starting with carbon-rich material, nitrogen-rich material, goat dung, top soil, rice husk, and cow urine up to the surface of the compost bin. All the materials were watered until saturated condition. Incubation of compost took time 1.5 months. Data collected during the incubation process were temperature, moisture content, population of soil fungi and soilworms, compost texture, colour, pH, and nitrogen (N), phosphorus (P), potassium (K) contents. The results were as followed: temperature 37°C, moisture content 62%, population of fungus ++, population of soilworm +, the color black to brown, texture coarse to fine, no stingy smell, pH 7.0, and high N, P, K levels. The conclusions were that the compost was high in quality, all qualitative and quantitative data were correlated with the standards of a high quality compost.